Deletion of Vhl in Dmp1-Expressing Cells Causes Microenvironmental Impairment of B Cell Lymphopoiesis - Chicana, Betsabel; Abbasizadeh, Nastaran; Burns, Christian; Taglinao, Hanna; Spencer, Joel A.; Manilay, Jennifer O. (Frontiers in Immunology, 2022)
The contributions of skeletal cells to the processes of B cell development in the bone marrow (BM) have not been completely described. The von-Hippel Lindau protein (VHL) plays a key role in cellular responses to hypoxia. Previous work showed that Dmp1-Cre;Vhl conditional knockout mice (VhlcKO), which deletes Vhl in subsets of mesenchymal stem cells, late osteoblasts and osteocytes, display dysregulated bone growth and reduction in B cells. Here, we investigated the mechanisms underlying the B cell defects using flow cytometry and high-resolution imaging. In the VhlcKO BM, B cell progenitors were increased in frequency and number, whereas Hardy Fractions B-F were decreased. VhlcKO Fractions B-C cells showed increased apoptosis and quiescence. Reciprocal BM chimeras confirmed a B cell-extrinsic source of the VhlcKO B cell defects. In support of this, VhlcKO BM supernatant contained reduced CXCL12 and elevated EPO levels. Intravital and ex vivo imaging revealed VhlcKO BM blood vessels with increased diameter, volume, and a diminished blood-BM barrier. Staining of VhlcKO B cells with an intracellular hypoxic marker indicated the natural existence of distinct B cell microenvironments that differ in local oxygen tensions and that the B cell developmental defects in VhlcKO BM are not initiated by hypoxia. Our studies identify novel mechanisms linking altered bone homeostasis with drastic BM microenvironmental changes that dysregulate B cell development.